Modelling HDV kinetics under the entry inhibitor bulevirtide suggests the existence of two HDV-infected cell populations - Shekhtman, Louis; Cotler, Scott J.; Degasperi, Elisabetta; Anolli, Maria Paola; Uceda Renteria, Sara Colonia; Sambarino, Dana; Borghi, Marta; Perbellini, Riccardo; Facchetti, Floriana; Ceriotti, Ferruccio; Lampertico, Pietro; Dahari, Harel (JHEP reports, 2024)
Bulevirtide (BLV) was approved for the treatment of compensated chronic hepatitis D virus (HDV) infection in Europe in 2020. However, research into the effects of the entry inhibitor BLV on HDV-host dynamics is in its infancy. Eighteen patients with HDV under nucleos(t)ide analogue treatment for hepatitis B, with compensated cirrhosis and clinically significant portal hypertension, received BLV 2 mg/day. HDV RNA, alanine aminotransferase (ALT), and hepatitis B surface antigen (HBsAg) were measured at baseline, weeks 4, 8 and every 8 weeks thereafter. A mathematical model was developed to account for HDV, HBsAg and ALT dynamics during BLV treatment. Median baseline HDV RNA, HBsAg, and ALT were 4.9 log IU/ml [IQR: 4.4-5.8], 3.7 log IU/ml [IQR: 3.4-3.9] and 106 U/L [IQR: 81-142], respectively. During therapy, patients fit into four main HDV kinetic patterns: monophasic (n = 2), biphasic (n = 10), flat-partial response (n = 4), and non-responder (n = 2). ALT normalization was achieved in 14 (78%) patients at a median of 8 weeks (range: 4-16). HBsAg remained at pre-treatment levels. Assuming that BLV completely (∼100%) blocks HDV entry, modeling indicated that two HDV-infected cell populations exist: fast HDV clearing (median t1/2 = 13 days) and slow HDV clearing (median t1/2 = 44 days), where the slow HDV-clearing population consisted of ∼1% of total HDV-infected cells, which could explain why most patients exhibited a non-monophasic pattern of HDV decline. Moreover, modeling explained ALT normalization without a change in HBsAg based on a non-cytolytic loss of HDV from infected cells, resulting in HDV-free HBsAg-producing cells that release ALT upon death at a substantially lower rate compared to HDV-infected cells. The entry inhibitor BLV provides a unique opportunity to understand HDV, HBsAg, ALT, and host dynamics. Mathematical modeling of hepatitis D virus (HDV) treatment with the entry inhibitor bulevirtide (BLV) provides a novel window into the dynamics of HDV RNA and alanine aminotransferase. Kinetic data from patients treated with BLV monotherapy can be explained by hepatocyte populations with different basal HDV clearance rates and non-cytolytic clearance of infected cells. While further studies are needed to test and refine the kinetic characterization described here, this study provides a new perspective on viral dynamics, which could inform evolving treatment strategies for HDV. [Display omitted] •Bulevirtide (BLV)’s mechanism of action provides a unique opportunity to understand the dynamics of HDV and HBV infection.•Assuming ∼100% blockage of HDV entry by BLV, mathematical modeling suggested that there are two populations of HDV-infected liver cells.•Modeling explained how ALT levels can normalize without a change in HBsAg levels under BLV.